FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK - Listyowati; Yuli Chomsatu Samrotun; Suhendro (Universitas Airlangga, 2018)
This study is to determine the influence of factors that comply with taxpayer compliance in paying taxes. The variables are sunset policy, tax amnesty, tax sanction, tax awareness, knowledge and understanding about taxes, and tax service as independent variable and taxpayer compliance as dependent variable. Population in this research is all of individual taxpayer registered in KPP Pratama Surakarta with sample used is 100. This study used questionnaires as a research instrument prepared by using Likert scale then analyzed using multiple regression processed with SPSS 17. The results obtained are sunset policy, tax amnesty, tax sanctions, knowledge and understanding of taxes, and tax service has no effect on taxpayer compliance. While tax payer awareness affect taxpayer compliance. The results of this study is expected to be the development of knowledge about taxation, especiallyabout taxpayer compliance in paying taxes. The results of this study are also expected to become a reference tax office to determine tax related policies to improve taxpayer compliance.